2019
DOI: 10.1021/acs.chemrev.8b00561
|View full text |Cite
|
Sign up to set email alerts
|

Metallomimetic Chemistry of Boron

Abstract: The study of main-group molecules that behave and react similarly to transition metal (TM) complexes has attracted significant interest in the recent decades. Most notably, the attractive idea of eliminating the all-too-often rare and costly metals from catalysis has motivated efforts to develop main-group-element-mediated reactions. Main-group elements, however, lack the electronic flexibility of many TM complexes that arise from combinations of empty and filled d-orbitals and that seem ideally suited to bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
166
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(173 citation statements)
references
References 310 publications
(482 reference statements)
1
166
0
6
Order By: Relevance
“…The synthesis and study of three-coordinate boron-containing compounds has led to the development of small molecule activators, [1] reagents, [2] catalysts, [3] sensors, [4] and optoelectronic devices. [5] These and other applications can be extended through discoveries of new reactivity enabled by ligand design (Figure 1).…”
mentioning
confidence: 99%
“…The synthesis and study of three-coordinate boron-containing compounds has led to the development of small molecule activators, [1] reagents, [2] catalysts, [3] sensors, [4] and optoelectronic devices. [5] These and other applications can be extended through discoveries of new reactivity enabled by ligand design (Figure 1).…”
mentioning
confidence: 99%
“…Of particular promise are boron-based molecules, which can activate small molecules and cleave stable covalentb onds. [3] Maier et al [4] synthesized the N 2 adducto fb orabenzene and Jin et al [5] observed B 3 (N 2 ) 3 + in the gas phase, which is stabilized throughd ative bondsb yN 2 .S imilarN 2 fixation to unstable borylenes under matrixc onditions was also detected by Edel et al [6] In all these instances, N 2 is coordinated in the terminal end-on mode with an early linear BÀNÀNa lignment.…”
Section: Introductionmentioning
confidence: 94%
“…However, owing to the scarcity, high cost, toxicity, and environmental issues associated with transition metals, main‐group metallomimetics has been regarded as an attractive alternative. Of particular promise are boron‐based molecules, which can activate small molecules and cleave stable covalent bonds . Maier et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[55,56] Neueste Arbeiten der Arbeitsgruppen Bertrand und Stephan sowie aus unserer Arbeitsgruppe demonstrierten den Singulettcharakter von Borylenen, die durch cyclische (Alkyl)-(amino)carbene stabilisiert sind. [55,56] Neueste Arbeiten der Arbeitsgruppen Bertrand und Stephan sowie aus unserer Arbeitsgruppe demonstrierten den Singulettcharakter von Borylenen, die durch cyclische (Alkyl)-(amino)carbene stabilisiert sind.…”
unclassified